2019
DOI: 10.3857/roj.2019.00633
|View full text |Cite
|
Sign up to set email alerts
|

Current status of proton therapy techniques for lung cancer

Abstract: Proton beams have been used for cancer treatment for more than 28 years, and several technological advancements have been made to achieve improved clinical outcomes by delivering more accurate and conformal doses to the target cancer cells while minimizing the dose to normal tissues. The state-of-the-art intensity modulated proton therapy is now prevailing as a major treatment technique in proton facilities worldwide, but still faces many challenges in being applied to the lung. Thus, in this article, the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 92 publications
1
35
0
Order By: Relevance
“…Considering the technical aspects, 88.7% of the patients in the present study received pencil beam scanning proton therapy. IMPT, which is based on the scanning beam technique, is expected to further improve the rate of normal organ sparing [ 19 ]. The treatment outcomes following IMPT re-irradiation were recently published [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the technical aspects, 88.7% of the patients in the present study received pencil beam scanning proton therapy. IMPT, which is based on the scanning beam technique, is expected to further improve the rate of normal organ sparing [ 19 ]. The treatment outcomes following IMPT re-irradiation were recently published [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For these clinical sites, advanced methods, such as MC simulations, can be beneficial. 188 MC calculations are also preferred over ADCs for dose calculations with IMPT systems degrading energy in the nozzle.…”
Section: A3 Accuracy and Limitations Of Analytical Dose Algorithmsmentioning
confidence: 99%
“…For complex geometries such as in head and neck and lung, approximations in ADC and its limited ability in modeling multiple‐Coulomb scattering can lead to geometric miss from overestimating the range or predicting unrealistic dose homogeneity caused by underestimation or overestimation of scatting effects in tissue. For these clinical sites, advanced methods, such as MC simulations, can be beneficial 188 . MC calculations are also preferred over ADCs for dose calculations with IMPT systems degrading energy in the nozzle.…”
Section: Radiotherapy Planning System Commissioningmentioning
confidence: 99%
“…With the rapid introduction and widespread usage of particle therapy, epidemiologically frequent tumors have been explored. The number of patients treated with proton therapy per year increased from 16,200 in 2015 to approximately 190,000 in 2018 and is expected to grow to be over 300,000 by 2030 (6). In 2014, Bush et al (7) reported the outcomes of proton therapy (PT) on 100 patients diagnosed with invasive non-lobular carcinoma and a maximal tumor dimension of 3 cm.…”
Section: Clinical Outcomes For Proton Therapymentioning
confidence: 99%